Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Methyl jasmonate alleviates chilling-induced browning in peach fruit through transcriptional suppression of PpLAC7 - Lufan Wang; Liang Zhou; Qiaocai Zhang; Huijuan Zhou; Lichao Zhou; Jiaxu Mao; Shiying Zhang; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Effects and Mechanism of Lactobacillus gasseri CCFM1346 Combined with Rutin on Alleviating Hyperuricemia in Mice - Xin Tang; Shuling Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

AcERF61 transcription factor mediates ethylene-induced kiwifruit softening through directly regulating cell wall degradation genes - Lufan Wang; Jiaxu Mao; Shiying Zhang; Huijuan Zhou; Libin Wang; Liang Zhou; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Boosting methanogenesis in high-solids anaerobic digestion of corn straw by coupling hydrogen nanobubbles with biochar - Chuanfei Bian; Yiming Shi; Mao Du; Shuaishuai Ma; Shiyu Li; Hao Liu; Luyao Wei; Shuling Cao; Binshou Wang; Hongliang Wang; Wanbin Zhu (Journal of Environmental Chemical Engineering, 2025)

Methyl jasmonate regulates the glycolytic pathway and the PpbZIP43-PpFAD2 module to enhance cold resistance in peach fruit - Lufan Wang; Yuxuan Wang; Jiaxu Mao; Huijuan Zhou; Libin Wang; Binger Dai; Liang Zhou; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Control efficiency and potential mechanisms of chlorogenic acid against postharvest gray mold caused by Botrytis cinerea on peach fruit - Binger Dai; Yuxuan Wang; Huijuan Zhou; Lufan Wang; Liang Zhou; Jiaxu Mao; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2024)

Absorption, metabolism, bioactivity, and biotransformation of epigallocatechin gallate - Shuling Zhang; Bingyong Mao; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Manufacturing maritime firms’ environmental behaviors: theory and practice - Shuling Mao; Yinxiao Xu (Frontiers in Marine Science, 2024)
Analyzing the factors that influence maritime manufacturing firms’ environmental behavior is of significant theoretical and practical importance, particularly from a managerial cognition perspective. This study applies the regulatory focus theory to examine the complex relationship between environmental quality, regulation, and firms’ environmental actions. Our findings reveal a U-shaped relationship between regional environmental quality and local firms’ environmental consciousness. In regions with either better or poorer environmental conditions, firms demonstrate higher environmental consciousness. Specifically, firms in regions with better environmental quality exhibit a “promotion focus” on environmental issues, leading to proactive engagement in green innovation. Conversely, firms in regions with poor environmental quality adopt a “prevention focus” by pursuing ISO 14001 certification to maintain legitimacy and mitigate penalties. Moreover, we find that incentive regulations are more effective at stimulating green innovation among firms operating in regions with good environmental quality. In contrast, mandatory regulations drive higher ISO 14001 certification rates among firms located in areas with poor environmental quality. This study offers insights into the internal and external motivators of firms’ environmental behavior, contributing to the literature on corporate environmental responsibility. Additionally, it provides policy recommendations to encourage active participation in environmental initiatives among maritime manufacturing firms.

Low-carbon technology service mode with revenue-sharing contract considering advance funding risk - Huiying Mao; Yuxia Guo; Yingyan Zhang; Shuling Zhou; Conghu Liu (Environmental Science and Pollution Research, 2022)